THE EFFECT OF TEMPERATURE AND MATERIAL SIZE ON THE PRODUCTION OF BIOCOAL BRIQUETTES MADE OF COAL LIGNITE, MERBAU SAWDUST, AND CORNCOB - Dewi, Dian Sari (KINETIKA, 2017)
The lignit charcoal, Merbau sawdust biomass waste and corncobs have a large potency and usage as an alternative of energy sources to replace the fossil energy such as crude oil and LPG. The aim of this research was ameliorating the quality of charcoal briquettes by adding the corncobs and Merbau sawdust waste in order to produce the biocoal, which is a better quality of briquettes as an alternative energy source. A proximate test was conducted to examine the biocoal briquettes in term of water content, ash content, volatile matter, fixed carbon, and heating value. The method used was varying the carbonization temperature (350oC, 400oC, and 500oC) for 60 minutes and varying the size of biocoal briquettes (20 mesh and 60 mesh). The results showed that the best biocoal briquettes were produced by 60 mesh sized briquettes in carbonization temperature of 500oC. However, the volatile matter values had not meet the requirement of SNI 01-6235-2000.